Association among muscle strength from upper and lower limb with risk of falls in elderly - Vívian Costa, Eva; de Paula Vieira, Rodolfo (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Falls represent a serious public health problem, especially for the elderly, and are associated with high rates of morbidity and mortality, decreased functional capacity, and early institutionalization. Falls have a multifactorial etiology, with muscle weakness being a significant risk factor. Objectives: To analyze the association between upper and lower limb muscle strength and the risk of falls in the elderly. Methods: This is a cross-sectional observational study with 81 individuals aged ≥ 60 years. Participants were subjected to the following assessment instruments International Physical Activity Questionnaire - IPAQ (short version), the Timed Up and Go Test (TUG), the handgrip strength test (HST), and the 30-second chair stand test. Results: Associations were observed between physical activity and HST (p = 0.004) and TUG (p = 0.010). Age was significantly associated with performance in the chair stand and rise test (p = 0.042) and TUG (p < 0.001). Multiple linear regression demonstrated that HST and age are predictors of the risk of falls. Conclusion: Low HST is a predictor of falls in the elderly (determined by TUG). Physically active elderly individuals had higher HST and a lower risk of falls compared to insufficiently active elderly individuals.